Once upon a time : a short history of fairy tale - Warner, Marina, 1946- (Oxford, United Kingdom : Oxford University Press, 2014)
Marina Warner has loved fairy tales over her long writing career, and she explores here a multitude of tales through the ages, their different manifestations on the page, the stage, and the screen. From the phenomenal rise of Victorian and Edwardian literature to contemporary children's stories, Warner unfolds a glittering array of examples, from classics such as Red Riding Hood, Cinderella, and The Sleeping Beauty, the Grimm Brothers' Hansel and Gretel, and Hans Andersen's The Little Mermaid, to modern-day realizations including Walt Disney's Snow White and gothic interpretations such as Pan's Labyrinth. In ten succinct chapters, Marina Warner digs into a rich collection of fairy tales in their brilliant and fantastical variations, in order to define a genre and evaluate a literary form that keeps shifting through time and history. She makes a persuasive case for fairy tale as a crucial repository of human understanding and culture.
The worlds of faery: Far away & down below -- With a touch of her wand: Magic & metamorphosis -- Voices on the page: Tales, tellers, & translators -- Potato soup: True stories/real life -- Childish things: Pictures & conversations -- On the couch: House-training the id -- In the dock: Don't bet on the prince -- Double vision: The dream of reason -- On stage & screen: States of illusion.
Includes bibliographical references (pages 181-193) and index.
Keywords: Fairy tales -- History and criticism; Fairy tales -- Adaptations; Fairy tales; Criticism, interpretation, etc